Role of Ammonium Bicarbonates in Methenogenesis While Co-digesting Petrochemical Wastewater with Activated Manure Sludge - Siddique, Md. Nurul Islam (Sila Science, 2013)
Inadequacy of nitrogenous reserve and buffering capability were acknowledged as regressive failure in former study treating petrochemical wastewater in anaerobic continuous stirred tank reactors. This study highlights the application of ammonium bicarbonate (NH4HCO3) as supplementation assuring nitrogenous resource and buffering requisite. To investigate the role of NH4HCO3 on the anaerobic degradation, a sequence of concentration up to 40 mg L-1 was observed. The outcome was assessed on the basis of biogas evolved. The investigation revealed that10 mg L-1 was the optimal without distressing methanogenesis. Likewise, mathematical calculation clarified that this optimum dosing can boost biogas yield up to 27.77% likened to control PWW degradation. Outcomes exposed an apparent commercial benefit to make the industrial application viable.